IDENTIFIKASI JENIS KAYU PERDAGANGAN DAN KURANG DIKENAL YANG DIPERDAGANGKAN DI SURABAYA - Nenny Sumarliani (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
Survey of commercial and lesser known wood species marketed in Surabaya has been conducted. The survey result from several companies shows that there are 21 commercial wood species represented by 10 families and 10 trade names. The trade name used in Surabaya is similar to those listed in the official Indonesian Timber nomen clature. A tentative identification key of the above wood species is presented in this paper.